First branchial cleft anomaly presenting with a complete duplication of the external auditory canal—A photo anatomic review. (March 2016) - Roche, Phoebe; Saunders, Stefanie; Naunheim, Mathew; Kovach, Alexandra; Herrington, Heather; Robson, Caroline D.; Whittemore, Kenneth R.
Abstract: First branchial cleft anomalies are an uncommon group of congenital malformations. Anatomically complex in origin, they present with an impressive array of signs and symptoms. There are several classification systems available, rendering them challenging in terms of preoperative assessment and surgical planning. The objective of this report is to describe the presentation, surgical treatment, and outcome of a child presenting with a complex cerumen containing duplication of the external ear canal running medial to the facial nerve. Diagnostic and management pitfalls in the approach to pediatric patients with first branchial anomalies are outlined. A review of the literature is presented.